PENGARUH STRUKTUR AUDIT, KONFLIK PERAN, KETIDAKJELASAN PERAN DAN INDEPENDENSI AUDITOR TERHADAP KINERJA AUDITOR (Studi Empiris Pada KAP di Pekanbaru, Padang dan Medan) (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
This study aimed to determine the effect of audit structure on the performance ofauditors, the performance of the auditors role conflict, role ambiguity on auditorsperformance and independence of the auditor to auditor performance.This study is a questionnaire survey with a distribution directly to the Office of PublicAccountants. The population around the auditor Public Accountant in Pekanbaru,Padang and Medan. Auditor sample totaled 88 people. The data analysis usingmultiple regression analysis using SPSS version 17:00. From the results of thetesting that has been done, parrsial regression test (t test) showed that the structureof the audit and role conflict had a significant impact on auditor performancevariables. The magnitude of the effect that (R2) by the audit structure variables, roleconflict, role ambiguity, and the independence of the auditors performance was54.7% /. While the remaining 45.3% is influenced by other variables not examined inthis study.Keywords:Audit structure, role conflict, role ambiguity, auditor independence andauditor performance